Roles of Microglia in AD Pathology - Rong, Gao; Hongrong, Wu; Qingqi, Li; Jianfeng, Zhao (Current Alzheimer Research, 2022)
Amyloid plaques and neurofibrillary tangles are two main characteristics of Alzheimer’s disease (AD). As cerebral resident phagocytes, microglia have different roles in Aβ pathology and tau pathology. In this review, we discuss microglial functions in the formation, clearance, and spread of Aβ and tau. Many receptors and enzymes, which are related to microglia, participate in AD pathologies and thus are thought to be potential targets of AD. So, making use of microglia can be beneficial to confine AD pathologies. To sum up, this article review the roles of microglia in AD pathology and possible corresponding treatments.
Keywords: Alzheimer’s disease